1997
DOI: 10.1021/ja963597k
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Carbon Monoxide Dehydrogenase fromClostridium thermoaceticumand Mechanism of Acetyl Coenzyme A Synthesis

Abstract: Carbon monoxide dehydrogenase from Clostridium thermoaceticum was methylated such that all bound methyl groups could subsequently react with CO and coenzyme A (or OH-) to yield acetyl-coenzyme A (acetyl-CoA) (or acetate). Methyl groups could not bind enzyme lacking the labile Ni of the A-cluster, but could bind such samples after incubation in aqueous Ni2+, a process known to reinsert the labile Ni and reactivate the enzyme. Bound methyl groups inhibited the ability of 1,10-phenanthroline to remove the labile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
151
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 63 publications
8
151
2
Order By: Relevance
“…However, we found that the EPR signal intensity was unchanged by the presence of a strong reductant (1 mM Ti 3ϩ -citrate). This indicates that disappearance of the NiFeC signal upon reaction with an appropriate methyl donor or during catalytic turnover (8,18,23) takes place by the reversal of reaction d, with the shift in equilibrium becoming favorable only in the presence of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the EPR signal intensity was unchanged by the presence of a strong reductant (1 mM Ti 3ϩ -citrate). This indicates that disappearance of the NiFeC signal upon reaction with an appropriate methyl donor or during catalytic turnover (8,18,23) takes place by the reversal of reaction d, with the shift in equilibrium becoming favorable only in the presence of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…This species was initially assumed to be the A-cluster itself, but Barondeau and Lindahl found that reductants unable to reduce A ox can effect methylation (50). Other known redox sites on the enzyme were also eliminated, suggesting that ACS Ct contains an unidentified n = 2 redox site which they called the D-site (not related to the D-cluster).…”
Section: -4 Electron Reduction (40)mentioning
confidence: 99%
“…Other mechanisms employ the A red -CO state as a catalytic intermediate (1), but there is evidence that this state inhibits catalysis (50,54). Further studies are required to resolve this.…”
Section: +mentioning
confidence: 99%
“…Another unusual feature of the A-cluster is that the ϩ1 state has been observed for both CODH⅐ACS (19) and ACS HT (20,21) only in complexes of the reduced enzymes with CO. There is agreement that CO (17) and the methyl group (8) bind to the Ni p site.…”
mentioning
confidence: 91%